Progestin treatment for the prevention of preterm birth - Lucovnik, Miha; Kuon, Ruben-Jeremias; Chambliss, Linda R.; Maner, William L.; Shi, Shao-Qing; Shi, Leili; Balducci, James; Garfield, Robert E. (Acta obstetricia et gynecologica Scandinavica, 2011)
Progestin supplementation appears to be a promising approach to both preventing initiation of preterm labor and treating it once it is already established, given the role of progesterone in maintaining pregnancy, as well as support from basic and clinical research. Progesterone and 17α-hydroxyprogesterone acetate slow the process of cervical ripening, and this is the rationale for prophylactic long-term progestin supplementation mostly studied so far. However, progesterone (but not 17α-hydroxyprogesterone acetate) also inhibits myometrial activity even after the cervix has already ripened. Moreover, these effects depend greatly on the vehicle used and the route of administration. Understanding different mechanisms of action, as well as the importance of progestin formulation, vehicle and route of administration, is the key to finding the optimal progestin treatment for prevention of preterm birth.
Gesehen am 11.11.2022